Analysis of Factors Affeecting Original Local Government Revenue (PAD) on the Island of Sumatra - Pangaribuan, Anggiat Marulitua; Azansyah, Azansyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Original Local Government (PAD) is one indicator of the independence of regional autonomy in an effort to explore potential and increase revenue sources. This study aims to analyze what factors affect Original local government (PAD). The factors analyzed are GDP Percapita, Number of Population, and Number of Tourists from 2013-2022 on the island of Sumatra. The data used in this study are Panel data with time series sequences from 2013 to 2022 and cross section data in Sumatra Province obtained from the Central Statistics Agency (BPS). The results of this study show that the variable GDP, population, has a positive and significant effect on PAD on the island of Sumatra, but the number of tourists has no effect and is not significant on PAD on the island of Sumatra.